FACTORS INFLUENCING THE INTEREST OF AGRIBUSINESS STUDENTS IN FARMERS' REGENERATION EFFORTS TO SUPPORT SUSTAINABLE AGRICULTURE - Nurlatipah, Syifa; Wafa, Azril; Anam, Faizal Khaerul; Wati, Dewi Rohma (Agripreneur : Jurnal Pertanian Agribisnis, 2024)
Regeneration of farmers is one of the important things for the sustainability of agriculture in Indonesia. However, currently the farming profession is dominated by older farmers compared to young farmers. The young generation's low interest in becoming farmers is a threat to the future of agriculture in Indonesia. Thus, this research aims to determine the influence of motivation, personality, family economy, and environmental conditions on agribusiness students' interest in the agricultural sector to support sustainable agriculture. This research was conducted at a university using the Accidental Sampling sampling method. The total sample was 100 Agribusiness students at universities in the Jakarta area which was calculated using the Lameshow formula.  Data were analyzed descriptively and quantitatively with Structural Equation Modeling Partial Least Square (SEM-PLS) analysis. Based on research results, motivation (X1), family economics (X2), and environmental conditions (X4) influence the interest (Y) of the younger generation in the agricultural sector. Meanwhile, personality (X3) has no significant effect on the interest (Y) of the younger generation in the agricultural sector.